2010
DOI: 10.1103/physreva.81.052313
|View full text |Cite
|
Sign up to set email alerts
|

Two-particle quantum walks applied to the graph isomorphism problem

Abstract: We show that the quantum dynamics of interacting and noninteracting quantum particles are fundamentally different in the context of solving a particular computational problem. Specifically, we consider the graph isomorphism problem, in which one wishes to determine whether two graphs are isomorphic (related to each other by a relabeling of the graph vertices), and focus on a class of graphs with particularly high symmetry called strongly regular graphs (SRG's). We study the Green's functions that characterize … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
181
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(186 citation statements)
references
References 33 publications
5
181
0
Order By: Relevance
“…Gudkov and Nussinov [12] proposed a classical algorithm to distinguish non-isomorphic graphs by mapping them onto various physical problems. Shiau et al proved that the simplest classical algorithm fails to distinguish some pairs of nonisomorphic graphs and also proved that continuous-time one-particle quantum random walks cannot distinguish some non-isomorphic graphs [13][14][15]. More recently, it has been found that classical random walks and quantum random walks can exhibit qualitatively different properties [16][17][18].…”
Section: The Graph Isomorphism Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Gudkov and Nussinov [12] proposed a classical algorithm to distinguish non-isomorphic graphs by mapping them onto various physical problems. Shiau et al proved that the simplest classical algorithm fails to distinguish some pairs of nonisomorphic graphs and also proved that continuous-time one-particle quantum random walks cannot distinguish some non-isomorphic graphs [13][14][15]. More recently, it has been found that classical random walks and quantum random walks can exhibit qualitatively different properties [16][17][18].…”
Section: The Graph Isomorphism Problemmentioning
confidence: 99%
“…There too, we find that it is sufficient to look at The largest size of graphs that we deal with analytically using perturbation theory is the family of 41 graphs having N = 29 vertices and signature (29,14,6,7). A scatterplot in the M x − Q 2 plane for this family is given in Fig.…”
Section: A Strongly Regular Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard benchmark for this approach is provided by the family of Strongly Regular Graphs (SRGs), that includes many hard instances of GI [6]. For example in [7][8][9] to distinguish non isomorphic graphs the authors exploit continuous [10][11][12] and discrete time quantum walks [13] of one or more particles moving through the graphs and compare the evolution of the same initial condition on the two graphs. The distinguishing power of the algorithm increases with the number of walker moving along the graph; the technique, however, is not universal and there are non-isomorphic graphs that cannot be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is hoped that two-particle quantum walks are more powerful than single-particle quantum walks. Much attention has been paid to multi-particle quantum walks and a lot of correlative algorithms have been proposed [6,[8][9][10].…”
mentioning
confidence: 99%